(untitled) (Indian Journal of Animal Production and Management, 2024)
Nellore breed is the most commonly reared sheep in the state of Andhra Pradesh. The present study was conducted to report the effect of age and physiological status on few blood biochemical parameters of Nellore sheep breed from the hot and humid areas of Andhra Pradesh. The present study was conducted to estimate the blood biochemical parameters and its effect on physiological parameters in Nellore sheep. The results evidenced significantly higher RBC, Hb in pregnant group compared to others. Significantly higher PCV values were recorded in the 0-1 age group of animals. The total protein, creatinine were significantly higher in the lactating group compared to the other two. The albumin levels were found to be significantly higher in pregnant group. The cholesterol, calcium, phosphorus levels were found to be significantly higher in 0-1 year group and decreased in periparturient period. The study established baseline values of Nellore sheep in the hot and humid areas of Andhra Pradesh and therefore can be used as reference values for further studies on these species. Biochemical parameters are important indicators of the health condition and metabolic activity irrespective of the physiological status of the animals. lactating animals. The variations in hematological parameters is multifactorial some of which are altitude, feeding level, age, sex, breed, diurnal and seasonal variation, temperature and physiological status of animals. The baseline values obtained from this study across different physiological status and age groups could be used as a reference for further experimentation on sheep located in these areas..